Takhrij and Syarah Hadith of Chemistry: Utilization of Miswak in Toothpaste - Abshar Fathur Rochman N; Nunung Kurniasih; Wahyudin Darmalaksana; Muhlas Muhlas (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet SAW. About the Utilization of Miswak in Toothpaste. This research method is qualitative through the approach of takhrij and syarah hadith with chemical analysis. The result and discussion of this study concluded that the use of miswak in toothpaste made teeth cleaner and protected from plaque for a long time. This study recommends developing the benefits of miswak through the chemical field